Individualized Tailor-Made Dietetic Intervention Program at Schools Enhances Eating Behaviors and Dietary Habits in Obese Hispanic Children of Low Socioeconomic Status. (29th January 2014) - Elizondo-Montemayor, Leticia; Moreno-Sànchez, Diana; Gutierrez, Norma G.; Monsivais-Rodriguez, Fabiola; Martinez, Ubaldo; Lamadrid-Zertuche, Ana C.; Hernandez-Torre, Martin M.
Abstract : Hispanic children and those from low-socioeconomic status are predisposed to unhealthy eating habits and obesity. Aim . to implement an individualized, face-to-face, parent supported, and school-partnership dietetic intervention to promote healthy eating habits and decrease body mass index. Prospective school year dietetic intervention of 101 obese, Hispanic, low-socioeconomic school-age children representative of Monterrey, Mexico, consisted of anthropometrics, dietetic assessment, energy-restriction tailor-made daily menus, and parental education every three weeks. Student's t -test was used for means comparison. A significant decrease was found in body mass index percentile ( 96.43 ± 3.32 to 93.42 ± 8.12 / P = 0.00 ) and energy intake/day of −755.7 kcal/day ( P = 0.00 ) . Among other energy dense foods with significant decline in servings/day and servings/week were processed meats ( 3.13 ± 1.43 to 2.19 ± 1.04 / P = 0.00 and 5.60 ± 1.75 to 4.37 ± 2.10 / P = 0.00, resp.), saturated fat ( 1.47 ± 1.08 to 0.78 ± 0.79 / P = 0.00 and 2.19 ± 2.18 to 1.1 ± 1.36 / P = 0.00 ), sweetened beverages ( 2.79 ± 1.99 to 1.42 ± 1.21 and 6.21 ± 1.72 to 3.89 ± 2.80 / P = 0.00 ), and desserts and refined-grain bakery ( 1.99 ± 1.54 to 1.32 ± 1.59 and 2.85 ± 2.54 to 1.57 ± 2.20 / P = 0.00 ) . There was a significant increase in servings/day and servings/week of water ( 2.98 ± 2.02 to 4.91 ± 2.37 and 6.62 ± 2.03 to 6.87 ± 0.91 / P = 0.00, resp.) and nutrient dense foods such as fruits ( 1 . 31 ± 0.89 to 1.66 ± 0.96 and 3.34 ± 2.24 to 4.28 ± 2.43 / P = 0.00 ) and fish and poultry ( 3.76 ± 2.15 to 4.54 ± 2.25 / P = 0.00 ) . This intervention created healthy eating habits and decreased body mass index in a high risk population. Trial registration number: NCT01925976 .